Anaphylactic shock management in dental clinics: An overview - Ronak S. Nanavati; Malay Kumar; Tapan G. Modi; Hemant Kale (Wolters Kluwer Medknow Publications, 2013)
Anaphylaxis is among the emergency clinical events specifi cally related to local anaesthesia, leading to morbidity and mortality. Hence, our aim is to update knowledge of dental professionals about management of this entity with appropriate emergency management, by giving proper pharmacotherapy to prevent further auto immune reaction thus, saving their lives.